Testování antibakteriálního účinku textilií ošetřených fotoaktivním ftalocyaninovým barvivem - Vrkoslavová, Jana; Bendová, Hana; Kejlová, Kristina; Kořínková, Radka; Kubáč, Lubomír; Martinková, Lenka (Chemické listy, 2021)
The aim of this study was to verify that textiles stained with photoactive phthalocyanine have antibacterial properties. 100% cotton and blended textiles (50% cotton/50% polyester) were tested. The tests were carried out with fabrics from production (maintenance-free) but also with textiles after several maintenance cycles. The quantitative method EN ISO 20743: 2014, namely the absorption method, was used and modified to assess the antibacterial properties of textiles. As models, we chose Escherichia coli as gram-negative bacteria and Enterococcus faecalis as gram-positive bacteria. It has been shown that the antibacterial effect occurs only in light activated fabrics stained with phthalocyanines. 100% cotton stained with phthalocyanine showed antibacterial properties even after 50 maintenance cycles prescribed for the healthcare sector, but the blended fabric showed no antibacterial properties after 10 maintenance cycles.